2003
DOI: 10.1046/j.1365-313x.2003.01762.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ethylene responsiveness in the Arabidopsis eer1 mutant results from a loss‐of‐function mutation in the protein phosphatase 2A A regulatory subunit, RCN1

Abstract: SummaryEthylene signaling in Arabidopsis begins with a family of ®ve ethylene receptors that regulate the activity of the Raf-like kinase, CTR1. Recent work to identify novel factors required for modulating ethylene signaling resulted in the isolation of enhanced ethylene response 1 (eer1), a mutant that displays both increased sensitivity and increased amplitude of response to ethylene. Molecular cloning of eer1 reveals that its mutant phenotype results from a loss-of-function mutation in the previously chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 41 publications
0
102
1
3
Order By: Relevance
“…PP2AA1 is considered to have a cardinal role in seedlings. Although morphologically similar to the wild type, PP2AA1 mutants display abnormal ethylene and ABA responses, as well as perturbed polar auxin transport [22][23][24][25] . PP2AA2 and PP2AA3 functions are unmasked only in a pp2aa1 mutant background 25 and neither pp2aa2 and pp2aa3 mutant nor pp2aa2-a3 double mutant plants have altered morphological phenotypes per se (see ref.…”
Section: Ton1mentioning
confidence: 95%
“…PP2AA1 is considered to have a cardinal role in seedlings. Although morphologically similar to the wild type, PP2AA1 mutants display abnormal ethylene and ABA responses, as well as perturbed polar auxin transport [22][23][24][25] . PP2AA2 and PP2AA3 functions are unmasked only in a pp2aa1 mutant background 25 and neither pp2aa2 and pp2aa3 mutant nor pp2aa2-a3 double mutant plants have altered morphological phenotypes per se (see ref.…”
Section: Ton1mentioning
confidence: 95%
“…EIR1 functions as an auxin transporter and may be a target for ethylene regulation of auxin transport to mediate gravitropic responses in the root (Luschnig et al, 1998). The eer1 mutant results from a loss-of-function mutation in the protein phosphatase 2A A regulatory subunit, RCN1 (Larsen and Cancel, 2003). This gene has also been implicated in regulating auxin responses in roots and abscisic acid signaling in guard cells (Garbers et al, 1996;Kwak et al, 2002) Figure 5.…”
Section: Ethylene Signaling Specificitymentioning
confidence: 99%
“…Subsequent biochemical characterization indicated that the PP2A catalytic subunit, PP2A-1C, interacts with the kinase domain of CTR1 but is not a phosphorylation substrate of CTR1. These findings led the authors to postulate that PP2A activity may modulate ethylene responses by altering CTR1 activity (Larsen and Cancel, 2003).…”
Section: Ethylene Signaling Specificitymentioning
confidence: 99%
“…The ETR1 receptor function can be regulated by RTE1 or the copper transporter RAN1 Resnick et al, 2006). ETR1 and ERS1 can interact with CTR1 that may be modulated by protein phosphatase 2A (Clark et al, 1998;Gao et al, 2003;Larsen and Cancel, 2003). Homologous genes of ethylene receptors have been isolated from many other plants, e.g.…”
mentioning
confidence: 99%